A kit based methodology for convenient formulation of 166Ho-Chitosan complex for treatment of liver cancer. (July 2020) - Lohar, Sharad; Jadhav, Sachin; Chakravarty, Rubel; Chakraborty, Sudipta; Sarma, Haladhar Dev; Dash, Ashutosh
Abstract: The effectiveness of 166 Ho-chitosan complex as a radiopharmaceutical for trans-arterial radiation therapy of liver cancer has been established in clinical trials. We have developed a simple kit-bade strategy for convenient formulation of therapeutically relevant doses of 166 Ho-chitosan complex in a hospital radiopharmacy in order to facilitate its widespread utilization. Quality control studies established the suitability of the radiopharmaceutical formulated using the developed strategy for in vivo administration. Biodistribution studies in normal Wistar rats showed excellent retention of the radiopharmaceutical in the liver, thus, paving the way towards utility of this approach in clinical context. Highlights: A two-vial kit has been developed for convenient formulation of therapeutically relevant dose of 166 Ho-chitosan complex. Therapeutically relevant dose of 166 Ho-chitosan complex was formulated with >97% yield and adequate stability. Biodistribution study in normal Wistar rat showed satisfactory retention of 166 Ho-chitosan complex in liver.